A comparative thermodynamic, economic and risk analysis concerning implementation of oxy-combustion power plants integrated with cryogenic and hybrid air separation units. (1st March 2015) - Skorek-Osikowska, Anna; Bartela, Łukasz; Kotowicz, Janusz
Highlights: Mathematical model of an integrated oxy-combustion power plant. Comparison of a hybrid membrane–cryogenic oxygen generation plant with a cryogenic plant. Thermodynamic analysis of the modeled cases of the plant. Comparative economic analysis of the power plant with cryogenic and hybrid ASU. Comparative risk analysis using a Monte Carlo method and sensitivity analysis. Abstract: This paper presents a comparison of two types of oxy-combustion power plant that differ from each other in terms of the method of oxygen separation. For the purpose of the analysis, detailed thermodynamic models of oxy-fuel power plants with gross power of approximately 460 MW were built. In the first variant (Case 1), the plant is integrated with a cryogenic air separation unit (ASU). In the second variant (Case 2), the plant is integrated with a hybrid membrane–cryogenic installation. The models were built and optimized using the GateCycle, Aspen Plus and Aspen Custom Modeller software packages and with the use of our own computational codes. The results of the thermodynamic evaluation of the systems, which primarily uses indicators such as the auxiliary power and efficiencies of the whole system and of the individual components that constitute the unit, are presented. Better plant performance is observed for Case 2, which has a net efficiency of electricity generation that is 1.1 percentage points greater than that of Case 1. For the selected structure of the system, an economic analysis of the solutions was made. This analysis accounts for different scenarios of the functioning of the Emission Trading Scheme and includes detailed estimates of the investment costs in both cases. As an indicator of profitability, the break-even price of electricity was used primarily. The results of the analysis for the assumptions made are presented in this paper. A system with a hybrid air separation unit has slightly better economic performance. The break-even price of electricity in this case is approximately 3.4 €/MW h less than for the system with a cryogenic unit. The main risk factors concerning implementation of such technologies were identified. The analysis of risk connected with the selection of these technologies was performed with the use of two methods – sensitivity analysis and a Monte Carlo method. The values of the probability were calculated, and the main results are presented and discussed in the paper.